Aracnidismo por Phoneutria en Costa Rica (Araneae: Ctenidae) - Trejos, Alfonso; Trejos, Roberto; Zeledón, Rodrigo (Revista de Biología Tropical, 1971)
The occurrence in Costa Rica of venomous spiders affecting man has recently been established, thanks to communication with rural workers through the "Instituto Centroamericano de Extensión de la Cultura" and its programs "Escuela para Todos" and "Almanaque ICECU". Several cases of people bitten by spiders identified as Phonentria were recorded from Guápiles, Pococí, Province of Limón and specimens of the species in question were obtained. Laboratory experiments with rats and mice revealed that the spiders possess a very active neurotoxic venom, which in one instance killed a mouse in six minutes. Treatment with analgesics and antihistamines proved successful in the two cases presented.